A spectroscopically confirmed Gaia-selected sample of 318 new young stars within ∼200 pc. Issue 1 (26th February 2021) - Žerjal, Maruša; Rains, Adam D; Ireland, Michael J; Zhou, George; Kammerer, Jens; Wallace, Alex; Orenstein, Brendan J; Nordlander, Thomas; Abbot, Harrison; Chang, Seo-Won
ABSTRACT: In the Gaia era, the majority of stars in the Solar neighbourhood have parallaxes and proper motions precisely determined while spectroscopic age indicators are still missing for a large fraction of low-mass young stars. In this work, we select 756 overluminous late K and early M young star candidates in the southern sky and observe them over 64 nights with the ANU 2.3-m Telescope at Siding Spring Observatory using the Echelle ( R = 24 000) and Wide Field spectrographs (WiFeS, R = 3000–7000). Our selection is kinematically unbiased to minimize the preference against low-mass members of stellar associations that dissipate first and to include potential members of diffuse components. We provide measurements of Hα and calcium H&K emission, as well as of Li i 6708 Å in absorption. This enables identification of stars as young as 10–30 Myr – a typical age range for stellar associations. We report on 346 stars showing detectable lithium absorption, 318 of which are not included in existing catalogues of young stars. We also report 125 additional stars in our sample presenting signs of stellar activity indicating youth but with no detectable lithium. Radial velocities are determined for WiFeS spectra with a precision of 3.2 km s −1 and 1.5 km s −1 for the Echelle sample.